2009
DOI: 10.1002/qua.21990
|View full text |Cite
|
Sign up to set email alerts
|

Band gaps and the possible effect on impact sensitivity for some nitro aromatic explosive materials

Abstract: ABSTRACT:The first principle density functional theory method SIESTA has been used to compute the band gap of several polynitroaromatic explosives, such as TATB, DATB, TNT, and picric acid. In these systems, the weakest bond is the one between an NO 2 group and the aromatic ring. The bond dissociation energy (BDE) alone cannot predicate the relative sensitivity to impact of these four systems correctly. It was found that their relative impact sensitivity could be explained by considering the BDE and the band g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 51 publications
0
47
0
Order By: Relevance
“…However, when the first principle density functional theory method SIESTA was used by Zhang et al [28] to compute the band gap of several polynitroaromatic explosives, such as 1,3,5-triamino-2,4,6-trinitrobenzene (TATB), 2,4,6-trinitro-1,3-benzenediamine (DATB), trinitrotoluene (TNT), and picric acid, the bond dissociation energy (BDE) alone cannot predict accurately the relative sensitivity to impact for these compounds. In these systems, the weakest bond was the one between an ANO 2 group and the aromatic ring.…”
Section: Bond Dissociation Energy Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when the first principle density functional theory method SIESTA was used by Zhang et al [28] to compute the band gap of several polynitroaromatic explosives, such as 1,3,5-triamino-2,4,6-trinitrobenzene (TATB), 2,4,6-trinitro-1,3-benzenediamine (DATB), trinitrotoluene (TNT), and picric acid, the bond dissociation energy (BDE) alone cannot predict accurately the relative sensitivity to impact for these compounds. In these systems, the weakest bond was the one between an ANO 2 group and the aromatic ring.…”
Section: Bond Dissociation Energy Methodsmentioning
confidence: 99%
“…[30][31][32][33][34] A quantitative structure-property relationship (QSPR) study was used by Wang et al [35] for prediction of impact sensitivity of nitramine, and a set of 35 molecular descriptors were calculated to represent its molecular structure. It was found that tunneling occurred from the ground state to excited states during the explosion of benzenoid molecules initiated by impact.…”
Section: Molecular Properties and Micromechanics Methodsmentioning
confidence: 99%
“…Zhang et al [31] explained well the trend of the impact sensitivity combining the band gap computed from the crystal with the BDE of NO 2 computed from the isolated molecule.…”
Section: Impact Sensitivity Of the Bchmxmentioning
confidence: 97%
“…Zhang and co-workers explained the correlation between bond dissociation energy, band gap and impact sensitivity for nitro-aromatic compounds. 38 Following the study, Zhu et al 39 also made a correlation between band gap and impact sensitivity of energetic materials (metal azides and styphanates, pure and K-doped CuN 3 , polymorphs of HMX, CL-20 and TATB) based on the Principle of Easiest Transition (PET), which states that with a smaller band gap it is easier to transfer the electron from valence band to conduction band. The calculated band gap for K 2 DNABT crystal is found to be 2.87 eV within PBE-GGA, which is 0.45 eV less that of the band gap value 2.42 eV 40 of α-lead azide (LA).…”
Section: Electronic Structure Chemical Bonding and Absorption Spementioning
confidence: 99%